DAMPAK SINETRON “IKATAN CINTA” DALAM PERKEMBANGAN MORAL ANAK DI DUSUN KETAON TENGAH - Aprilia Putri Kusuma (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This article aims at : (1) identifying the effects of watching the electronic cinema “Ikatan Cinta” on the moral development of children in Dusun Ketaon Tengah, (2) identifying the role of parents in accompanying children to watch television programs, (3) identifying efforts or ways parents anticipate the effect of electronic cinema, and (4) analizyng parental responses to electronic cinema “Ikatan Cinta”. Metod applied in research is descriptive method, because the collecting data related to the describe of data to answer questions about the subject to be studied. The effect of watching electronic cinema can be seen from changes in aggressive behavior, speaking style, and dressing style. Parents have an important role to instilling religious values, habits, and moral values in children. A critical attitude and assinstance from parents can help children in their moral development so that they can behave well. The existence of television is expected to a positive impact, by broadcasting abjective, sharp, and reliable information.